The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/modpathol.2017.59
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 immunohistochemistry in clinical diagnostics of lung cancer: inter-pathologist variability is higher than assay variability

Abstract: Assessment of programmed cell death ligand 1 (PD-L1) immunohistochemical staining is used for decision on treatment with programmed cell death 1 and PD-L1 checkpoint inhibitors in lung adenocarcinomas and squamous cell carcinomas. This study aimed to compare the staining properties of tumor cells between the antibody clones 28-8, 22C3, SP142, and SP263 and investigate interrater variation between pathologists to see if these stainings can be safely evaluated in the clinical setting. Using consecutive sections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
143
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(166 citation statements)
references
References 26 publications
8
143
0
Order By: Relevance
“…Studies regarding the prognostic impact of PD-1 and PD-L1 expression have used different categorical cut-offs, 16-21 some also including staining intensity, and no consensus has yet been reached regarding an optimal prognostic cut-off. For evaluation of tumour cell-specific PD-L1 expression, we applied cut-offs commonly used in clinical studies 46 and the prognostic value of PD-1 + immune cells was validated using the total count. The results from the present study, demonstrating that immune cell-specific PD-1 and PD-L1 expression carries the most evident prognostic value in right-sided CRC, are not likely to be disputed by alternative scoring systems.…”
Section: Discussionmentioning
confidence: 99%
“…Studies regarding the prognostic impact of PD-1 and PD-L1 expression have used different categorical cut-offs, 16-21 some also including staining intensity, and no consensus has yet been reached regarding an optimal prognostic cut-off. For evaluation of tumour cell-specific PD-L1 expression, we applied cut-offs commonly used in clinical studies 46 and the prognostic value of PD-1 + immune cells was validated using the total count. The results from the present study, demonstrating that immune cell-specific PD-1 and PD-L1 expression carries the most evident prognostic value in right-sided CRC, are not likely to be disputed by alternative scoring systems.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the scoring of immune cells yields low concordance rates and that IHC is probably inadequate for assessment of immune cell expression independent of which assay is selected, with only the possible exception of the SP142 clone, specifically developed for evaluation of tumor associated immune cells (7). Conversely, several studies summarized in Table 1, consistently reported a relatively good agreement for PD-L1 scoring between the pathologists, independent of training and professional education (3,(7)(8)(9)(10).…”
Section: Editorialmentioning
confidence: 99%
“…There is limited data assessing the reproducibility of interpretation and scoring of PD-L1 expression in NSCLC tissue samples and most studies only involve a few pathologists or small numbers of tumors, making it easy to achieve concordance (12)(13)(14)(15)(16). Whereas some studies assessed PD-L1 interpretation reproducibility on resection specimens, only a few studies used smaller sized specimens such as tissue micro-arrays, but none on bronchial or transthoracic biopsies (12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…Similarly, a recent study showed that up to 20% of the analyzed cases were differently classified as positive or negative by any pathologist compared with the gold standard using the cut point ≥1% TPS, whereas there was better agreement between pathologists using the cut point ≥50% TPS (0-5% of cases) (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation